High Performance Generation of H2O2 under Piezophototronic Effect with Multi‐Layer In2S3 Nanosheets Modified by Spherical ZnS and BaTiO3 Nanopiezoelectrics. Issue 6 (22nd April 2021) - Zhou, Xiaofeng; Shen, Bo; Zhai, Jiwei; Conesa, José C.
Abstract: Manipulating the separation and transportation of photoexcited charge carriers in photoresponsive semiconductors via the piezoelectric polarization effect is an emerging strategy in the field of artificial photosynthesis. However, existing semiconductor photocatalysts, both with a wide range absorption for visible light and superior piezoelectricity are very scarce, leading to a low reactivity of photocatalysis. Here, a multi‐layer In2 S3 nanosheet modified with spherical ZnS and BaTiO3 nanopiezoelectrics (ZnS/In2 S3 /BTO) is reported, generating approximately 378 µm of H2 O2 in 100 min (and the concentration is still increasing) under co‐irradiation of visible light and ultrasound (piezophotocatalysis) in ethanol–water solution; this concentration is higher compared with two phases piezoelectric heterostructures (i.e., ZnS/BTO, In2 S3 /BTO, and ZnS/In2 S3 ) and pure compounds (i.e., ZnS, In2 S3, and BTO), and also higher than that of independent piezo‐ (≈254 µm ) and photocatalysis (≈120 µm ). Moreover, the concentration of H2 O2 generated on ZnS/In2 S3 /BTO can be as high as approximately 1160 µm in 5 h of piezophotoreaction after experiencing six cycles of visible light concurrent with ultrasound irradiation. The enhancement of H2 O2 yield on ZnS/In2 S3 /BTO in piezophotocatalysis can be attributed to the piezopotential‐induced internal electric polarization field promoting the separation of photoexcited charge carriers, thus boosting the rate of surface photoreaction. Abstract : Piezopotentials allow to tune surface charges on piezoelectric semiconductors via vibration energy. Implementation of surface engineering causes strong increases in catalytic activity and selectivity on photocatalysts, but no efficient reactivity is obtained yet. A polarization field is built in piezoelectric ZnS/In2 S3 /BaTiO3 to promote effective separation and transfer of photogenerated electron–hole pairs enhancing the catalytic surface reactions for H2 O2 production.